Upper limb recovery in spinal cord injury: involvement of central and peripheral motor pathways - Petersen, Jens; Weidner, Norbert; Rupp, Rüdiger (Neurorehabilitation and neural repair, 2017)
Background and Objective. The course of central and peripheral motor recovery after cervical spinal cord injury (SCI) may be investigated by electrophysiological measures. The goal of this study was to compare the 2 over the first year after injury in relation to motor gains. Methods. Compound motor action potentials (CMAPs), motor-evoked potentials (MEPs), and F-waves were recorded from the abductor digiti minimi and CMAP and F-waves from abductor hallucis muscles in 305 patients at about 15 days, 1 month, 3 months, 6 months, and 12 months following an acute traumatic SCI. Results. The MEP amplitudes and F-wave persistences were lower with more severe sensorimotor impairment. They steadily increased in most subgroups within 6 months after SCI. The amplitude of the CMAPs was low for the first 3 months in the most severely affected participants. This was also found for CMAPs from tibial nerve originating well below the cervical lesion level. Improvement in neurophysiological parameters correlated with improved upper extremity motor scores. Conclusion. The results point to a systematic interrelation of corticospinal transmission, spinal motoneuron excitability, and its axon function, respectively. Electrophysiological correlates of neural excitability show distinct spatial and temporal interrelations within central and peripheral motor pathways following acute cervical SCI. A strong secondary deterioration within the peripheral motor system with incomplete or no recovery depends on anatomical distance caudal to lesion and on lesion severity. Electrophysiological assessments may increase the sensitivity of interventional studies in addition to clinical measures.